ASSOCIATION BETWEEN URIC ACID AND PULSE WAVE VELOCITY IN HYPERTENSIVE PATIENTS AND GENERAL POPULATION: A SYSTEMATIC REVIEW AND META-ANALYSIS. (April 2021) - Maloberti, Alessandro; Rebora, Paola; Andreano, Anita; Triglione, Nicola; Piccinelli, Enrico; Palazzini, Matteo; Occhi, Lucia; Sun, Jinwei; De Chiara, Benedetta; Grassi, Guido; Valsecchi, Grazia; Giannattasio, Cristina
Abstract : Objective: The association between Serum Uric Acid (SUA) and Pulse Wave Velocity (PWV), has been extensively evaluated but with some discrepancies in results. A further limitation refers to the fact that only few data were analyzed taking into account the possible effects of gender. The purpose of this study was to estimate the association between SUA and arterial stiffness in general population and hypertensive patients, as a whole population and as divided by gender, by pooling results from existing studies. Design and method: Carotid-femoral and brachial-ankle PWV (cf- and ba-PWV) have been analysed separately and subgroup analyses by gender are reported. Results: Among 692 potentially relevant works, 24 paper were analysed. 7 studies referred to cf-PWV in the general population with an overall positive association at adjusted analysis for both males and females (0.07 - 95%CI: 0.03; 0.11 and 0.06 - 95%CI: 0.03; 0.09, respectively). 12 studies referred to ba-PWV in the general population with the finding of a positive association at adjusted analysis for females (0.04 - 95%CI: 0.01;0.07), but not for males (0.13 - 95%CI: -0.09;0.34). In hypertensive patients only 4 studies evaluated cf-PWV and 1 ba-PWV with only one study (with cf-PWV) finding positive association. Conclusions: The association between SUA and cf-PWV resulted significant in general population in both males and females while it was only significant for female regarding ba-PWV. Furthermore, the few available studies found no significant relationship between SUA and both cf- and ba-PWV in hypertensive subjects.